The role of collagenase ointment in acute burns: a systematic review and meta-analysis. (1st February 2019) - Pham, Christopher H; Collier, Zachary J; Fang, Mike; Howell, Anna; Gillenwater, Timothy J
Abstract : Objective: A systematic review and meta-analysis was performed to summarise the state of the literature in regard to the efficacy and uses of clostridial collagenase ointment (CCO) in the burn patient. Method: A systematic review of articles available on PubMed, Scopus and OvidSP Medline was performed. Keywords used in the search process included burns, thermal injury, collagenase, enzymatic debridement, wound care. Reviews, case reports, independent abstracts, consensus and opinion papers were excluded. A meta-analysis was performed for articles fitting inclusion criteria. Results: Following screening, six relevant articles were identified for systematic review. Few studies, with limited sample sizes, argue that CCO may be an effective debriding agent. It may also accelerate wound healing and avoid the pain associated with mechanical debridement. CCO lacks antimicrobial activity but the risk of burn wound infection does not appear to be significantly different than when using silver-impregnated products. CCO is more expensive than traditional wound care products but may help halt burn depth conversion and prevent the need for surgery. Conclusion: CCO may be a safe and effective debridement agent for burn wounds with respect to decreasing wound healing time and minimising pain without increasing the risk of infection. It should be used on a case-by-case basis due to its financial cost, which may be offset by its ability to manage burns non-operatively.